Risperidone-induced neuroleptic malignant syndrome: a case report - Ling Deng; Zhi-Xin Qiu; Mao-Yun Wang (SAGE Publishing, 2022)
Neuroleptic malignant syndrome (NMS) is a rare illness that results from reactions to antipsychotics. However, the diagnosis of NMS is challenging due to its atypical clinical presentation and unclear pathogenesis. We report the case of a patient with NMS induced by irregular use of antipsychotics, especially risperidone (RSP). He had typical hyperthermia, muscle rigidity and rhabdomyolysis, which led to renal impairment. We carefully analysed the mechanism by which NMS occurred in this patient. An interesting aspect of the case is the synergistic involvement of risperidone, antidepressants, opioids and stress. Because of these complex predisposing factors, it is difficult to completely rule out the diagnosis of malignant hyperthermia (MH). In addition, the rare phenomenon of elevated lipase and amylase was observed in this patient.